Investigation of the relationship between neuroplasticity and grapheme-color synesthesia - Eckardt, Nadine; Sinke, Christopher; Bleich, Stefan; Lichtinghagen, Ralf; Zedler, Markus (Frontiers in Neuroscience, 2024)
Grapheme-color synesthesia is a normal and healthy variation of human perception. It is characterized by the association of letters or numbers with color perceptions. The etiology of synesthesia is not yet fully understood. Theories include hyperconnectivity in the brain, cross-activation of adjacent or functionally proximate sensory areas of the brain, or various models of lack of inhibitory function in the brain. The growth factor brain-derived neurotrophic (BDNF) plays an important role in the development of neurons, neuronal pathways, and synapses, as well as in the protection of existing neurons in both the central and peripheral nervous systems. ELISA methods were used to compare BDNF serum concentrations between healthy test subjects with and without grapheme-color synesthesia to establish a connection between concentration and the occurrence of synesthesia. The results showed that grapheme-color synesthetes had an increased BDNF serum level compared to the matched control group. Increased levels of BDNF can enhance the brain's ability to adapt to changing environmental conditions, injuries, or experiences, resulting in positive effects. It is discussed whether the integration of sensory information is associated with or results from increased neuroplasticity. The parallels between neurodegeneration and brain regeneration lead to the conclusion that synesthesia, in the sense of an advanced state of consciousness, is in some cases a more differentiated development of the brain rather than a relic of early childhood.